2013
DOI: 10.4240/wjgs.v5.i6.173
|View full text |Cite
|
Sign up to set email alerts
|

Caudal approach to pure laparoscopic posterior sectionectomy under the laparoscopy-specific view

Abstract: AIM:To study our novel caudal approach laparoscopic posterior-sectionectomy with parenchymal transection prior to mobilization under laparoscopy-specific view. METHODS:Points of the procedure are: (1) Patients are put in left lateral position and posterior sector is not mobilized; (2) Glissonian pedicle of the sector is encircled and clamped extra-hepatically and divided afterward during the transection; (3) Dissection of inferior vena cava (IVC) anterior wall behind the liver is started from caudal. Simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…From these experiences, we propose the following advantages of laparoscopic hepatectomy for HCC patients: (1) advantageous for repeat procedures: Repeat pure laparoscopic hepatectomy (and combined treatments) for patients with liver cirrhosis and multicentric/ metachronous HCCs was feasible and safe. The procedure also resulted in less post-operative adhesion and good vision and manipulation in the small area between the adhesions (case 1, Figures 1 and 2); (2) minimal invasion due to good vision: With adequate port arrangement and positioning of the patients [41,42] , the manipulation in the small operative field is facilitated by good vision of the peri-inferior vena cava (IVC) area, subphrenic space, the area next to the attachment of retro-peritoneum, and the area between the adhesions. Therefore, there is a minimum need for dissection and/or adhesiolysis that could cause destructions of the collateral blood and lymphatic flows (case 2, Figures 3 and 4; case 3, Figures 5 and 6); and (3) better control of bleeding: Instead of compression and elevation of the bleeding field, other techniques are employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these experiences, we propose the following advantages of laparoscopic hepatectomy for HCC patients: (1) advantageous for repeat procedures: Repeat pure laparoscopic hepatectomy (and combined treatments) for patients with liver cirrhosis and multicentric/ metachronous HCCs was feasible and safe. The procedure also resulted in less post-operative adhesion and good vision and manipulation in the small area between the adhesions (case 1, Figures 1 and 2); (2) minimal invasion due to good vision: With adequate port arrangement and positioning of the patients [41,42] , the manipulation in the small operative field is facilitated by good vision of the peri-inferior vena cava (IVC) area, subphrenic space, the area next to the attachment of retro-peritoneum, and the area between the adhesions. Therefore, there is a minimum need for dissection and/or adhesiolysis that could cause destructions of the collateral blood and lymphatic flows (case 2, Figures 3 and 4; case 3, Figures 5 and 6); and (3) better control of bleeding: Instead of compression and elevation of the bleeding field, other techniques are employed.…”
Section: Introductionmentioning
confidence: 99%
“…These include meticulous manipulation under magnifying view, pressure control of pneumo-peritoneum and IVC, and various coagulating devices [43] . The ability of bleeding control is becoming matched to open surgery and anatomical hepatectomies with the exposure of major vessels recently becoming feasible [41,[44][45][46][47][48] . The major disadvantages of laparoscopic surgery are in compression of the bleeding point, palpitation of scopic hepatectomy is the better therapeutic option for severe cirrhotic patients with tumors on the surface of the liver, in case of difficult adaptation of percutaneous ablation therapy and/or local recurrence after repeat treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, patients who have huge tumors located in the right lobe of liver, or tumors with infiltration to the diaphragm or the IVC, are more suitable for the CDA than the CA because in the CA, inappropriate mobilization can readily result in massive bleeding and tumor cell dissemination. 24 Tomishige et al 32 performed laparoscopic posterior sectionectomy using the CDA successfully to resect a 1.5-cm metastatic lesion in segment 6 near the RHV. They concluded that the CDA is useful for patients who have tumors close to the RHV and that exposure of the RHV is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our previously extensive experience in laparoscopic liver resections 2,29,30 and encouraging literature results of the anterior approach in open right hepatectomy [23][24][25][26] have led us to focus on the CDA in LRH. To our knowledge, few studies 27,[31][32][33][34] have mentioned the anterior approach or the novel CDA in LRH or other major laparoscopic liver resections. In this series, we report our preliminary operative and postoperative findings on the safety and feasibility of the CDA compared with the conventional approach (CA) in LRH.…”
Section: Introductionmentioning
confidence: 97%
“…[5][6][7] It is becoming clear that the magnified caudal view offered by laparoscopy allows improved visualization, especially for the hilar and dorsal area of the liver, and is thus beneficial for the dissection of hilar Glissonian pedicles and the inferior vena cava (IVC). [7][8][9] LLRs of major hepatectomy and, even, with combined resection of major hepatic veins are now increasingly reported, [10][11][12] despite the latter previously being a contraindication. Reports of repeated LLR procedures [13][14][15][16] are also increasing.…”
Section: Introductionmentioning
confidence: 99%